Effects of long-term exposure to colloidal gold nanorods on freshwater microalgae - Monteiro, Cátia (2019)
Gold nanorods have shown to pose adverse effects to biota. Whether these effects may be potentiated through prolonged exposure has been rarely studied. Therefore, this work aimed at evaluating the effects of long-term exposure to sublethal levels of cetyltrimethylammonium bromide (CTAB) coated gold nanorods (Au-NR) on two freshwater microalgae: Chlorella vulgaris and Raphidocelis subcapitata. These algae were exposed to several concentrations of Au-NR for 72 h and, afterwards, to the corresponding EC5,72h, for growth, during 16 days. The sensitivity of the two algae to Au-NR was assessed at days 0, 4, 8, 12 and 16 (D0, D4, D8, D12 and D16, respectively) after a 72-h exposure to several concentrations of Au-NR. At the end of the assays, effects on yield and population growth rate were evaluated. Raphidocelis subcapitata was slightly more sensitive to Au-NR than C. vulgaris: EC50,72h,D0 for yield were 48.1 (35.3-60.9) and 70.5 (52.4-88.6) μg/L Au-NR, respectively while for population growth rate were above the highest tested concentrations (53 and 90 μg/L, respectively). For R. subcapitata the long-term exposure to Au-NR increased its sensitivity to this type of nanostructures. For C. vulgaris, a decrease on the effects caused by Au-NR occurred over time, with no significant effects being observed for yield or population growth rate at D12 and D16. The capping agent CTAB caused reductions in yield above 30% (D0) for both algae at the concentration matching the one at the highest Au-NR tested concentration. When exposed to CTAB, the highest inhibition values were 69% (D4) and 21.3% (D8) for R. subcapitata, and 64% (D12) and 21% (D16) to C. vulgaris, for yield and population growth rate, respectively. These results suggested long-term exposures should be included in ecological risk assessments since short-term standard toxicity may either under- or overestimate the risk posed by Au-NR.